ANTECEDENTS OF SMARTPHONE PURCHASE INTENTION - Safira Hanief Mardhotillah; Bentang Khoerunnisa; Aang Curatman (IJEBD (International Journal of Entrepreneurship and Business Development))
Purpose: The objective of this study is to examine and explain (1) how brand image affects purchase intention and (2) how brand image affects customer satisfaction. (3) how purchase intention is impacted by customer satisfaction; (4) how purchase intention is impacted by online customer reviews (5) Customer satisfaction acts as a mediator in the link between purchase intention and brand image.